Evaluating Quality of Second-Stage Labor Care. Issue 5 (September 2016) - Simpson, Kathleen Rice
Abstract : The condition of the baby at birth is a potentially valuable indicator of the quality of care during the second stage of labor. Consider using Apgar scores less than 7 at one minute as criteria for selecting cases for team review. Use the lessons learned to change practice accordingly.